2018
DOI: 10.3389/fneur.2018.00827
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Particulate Air Pollution on Ischemic Stroke and Hemorrhagic Stroke Mortality

Abstract: Background and Purpose: A large body of literature reported the association of particulate matter (PM) with stroke in high-income countries. Few studies have examined the association between PM and stroke in middle- and low-income countries and considered the types of stroke. In this study, we examined the short-term effects of particulate matter <2.5 μm in diameter (PM2.5) and particulate matter <10 μm in diameter (PM10) on ischemic stroke mortality and hemorrhagic stroke mortality in Beijing, China.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
(47 reference statements)
2
35
1
Order By: Relevance
“…In the present study, there was no association between PM concentration and stroke in cancer survivors. Both hemorrhagic and ischemic stroke risk were increased in cancer patients [47,48] even after 10 years of surviving [49] in previous studies. This phenomenon may need to be investigated further.…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, there was no association between PM concentration and stroke in cancer survivors. Both hemorrhagic and ischemic stroke risk were increased in cancer patients [47,48] even after 10 years of surviving [49] in previous studies. This phenomenon may need to be investigated further.…”
Section: Discussionmentioning
confidence: 61%
“…For example, studies have found an association between PM 10 and multiple sclerosis including etiology [44] as well as with relapse [45]. PM 10 has also been associated with ischemic stroke mortality [46]. PM 10 has been shown to stimulate lung inflammation and endothelial injury [47] and encourage atherosclerosis [48].…”
Section: Plos Onementioning
confidence: 99%
“…As a potentially modifiable risk factor, the effects of air pollution on human health are a topic that has received much attention in recent decades. A large body of epidemiological and clinical studies supports the existence of positive associations between air pollution and the morbidity and mortality of ischemic stroke, as well as hemorrhagic stroke (Andersen et al 2012;Huang et al 2019;Sun et al 2019;Zhang et al 2018). According to the International Classification of Diseases (ICD), both transient ischemic attack (TIA) and stroke are categorized as cerebrovascular disorders (Bo Norrving et al 2013;Sacco et al 2013).…”
Section: Introductionmentioning
confidence: 99%